Digital Advocacy Phenomenon in ASEAN (Case Study: The Social Movement of Milk Tea Alliance in Thailand and Myanmar) - Hendy Achmad Reynaldi; Carakawidya Gusni Dhiyaa; Riswanda Imawan (Nusantara Science and Technology Proceedings, 2022)
Milk Tea Alliance has gained its popularity as broad youth protests trans- cending national borders against authoritarianism. The protests started to spread its influence in Far-Eastern countries like Hongkong and Taiwan in 2020. In a matter of months, Milk Tea Alliance quickly broadened its influence reaching Southeast Asian countries, namely Thailand and Myanmar. This research aimed to explain the processes of Milk Tea Alliance advocacy as a social movement in ASEAN settings, especially in Thailand and Myanmar. Methodologically, most secondary data are collected with library research techniques and analyzed explanatively with an integrated framework of analysis consisting of a transnational advocacy network model and digital advocacy concept. This research found that Milk Tea Alliance operates transnationally—by disseminating information, framing public opinion, and gaining mass support—and digitally with the help of social media. The results of the research have implications for the overview of digital advocacy practice in ASEAN.